ALGORITHMS FOR IDENTIFYING DRUG-RESISTANCE MUTATIONS IN M. TUBERCULOSIS GENOMES - R. S. Sergeev; I. S. Kavaliou; A. V. Tuzikov; A. Rosenthal; A. Gabrielian (Informatika)
Analysis of whole-genome sequences often leads to problems of large dimensionality where the number of parameters exceeds the number of available observations. We offer methodology of genome-wide association study and investigate various approaches to assess contribution of mutations in the emergence and development of drug resistance in Mycobacterium tuberculosis. We present the results of our experiments aimed at identifying resistance mutations to the major anti- TB drugs based on data obtained from patients in Belarus.